The impact of judicial control on the public administration of the environment : 1995 to 2007 - Hall, Jennifer Helen (Department of Public Law, 2014)
This thesis sets out the findings of an empirical study on three environmental departments' responses to judicial regulation during the first fifteen years of democracy.